Women, Identity and Private Life in Britain, 1900–50 - Gamble, Andrew. author. aut Link
VIII, 189 p.
Keywords: Women, Identity and Private Life in Britain, 1900-50, explores the meanings and experience of home and private life for women who grew up in England before 1950. It considers the extent to which class, suburbanisation and historical moment as well as gender constructed women's understanding of domesticity, and discusses the part played by conceptions of home and private life in the shaping of identities. Oral narratives, fiction, autobiography and diaries are used in conjunction with psychoanalytic, linguistic and historical explanations of women's lives to map a psychological as well as a social history of women's relationship to the home in the early part of this century.